Pengaruh Good Corporate Governance, Capital Intensity, Proftabilitas Terhadap Agresivitas Pajak - Sihombing, Sustresia; Indra Pahala; Diah Armeliza (Jurnal Akuntansi, Perpajakan dan Auditing, 2021)
This research aims to examine the effect of Good Corporate Governance, Capital Intensity, and Profitability on Tax Aggressiveness. This research uses secondary data with purposive sampling technique selected as many as 165 samples, data from all companies except the financial sector listed on the Indonesia Stock Exchange in 2020 and processed using multiple linear regression analysis with the help of software IBM SPSS statisticalcs 20. Tax aggressiveness in this research was measured by ETR. The results of this research found that the variable Institutional Ownership has no effect on tax aggressiveness. Independent commissioners and audit committees have an effect on tax aggressiveness, which means that supervision from independent commissioners and audit committees will prevent opportunistic actions from management in terms of tax aggressive behavior. Capital Intensity and Profitability have no effect on tax aggressiveness. Keywords: Good Corporate Governance, Capital Intensity, Profitability, and Tax Aggressiveness